Pengaruh Citra Merek, Komunikasi Merek, Kewajaran Harga Dan Perceived Quality Terhadap Loyalitas Merek Pasta Gigi Nasa Pada Konsumen Di Kota Purbalingga - Roikha Nurjanah; Arinastuti Arinastuti; Andhi Johan Suzana (Majalah Imiah Manajemen & Bisnis, 2022)
In achieving company goals, human resources play a very important role. The organization will thrive if supported by loyal and highly committed employees, which is shown by their attitudes and behavior in the workplace. Positive behavior of employees or members of the organization can support individual performance and organizational performance for better organizational development. Organizational Citizenship Behavior (OCB) is a voluntary employee behavior that is not directly related to the compensation, but contributes to the effectiveness of the organization. OCB is vital for an effective organization because it includes behavior that is not directly related to performance tasks but is important for overall organizational performance. Organizational Citizenship Behavior (OCB) plays a key role in supporting the effectiveness of organizational functions, especially in the long run. The purpose of this research is to find out the extent of OCB UMKM of Kabupaten Banyumas The approach used in this study is quantitative method with a mean score to measure employee OCB on obedience, loyalty and participation. The results of the study concluded that the three indicators used in the assessment show good average score. Of the three indicator values the smallest is the value of the participation indicator with 3.39. The lack of OCB values from participation indicator shows the degree of OCB held by UMKM Kabupaten Banyumas so that the institution can design trainings or workshops that are in accordance with employee needs so that employees can exhibit work behavior that exceeds standards.